Clinotron: a Promising Source for THz Regions - Manzhos, S.; Schuenemann, K.; Sosnytskiy, S.V.; Vavriv, D.M. (Радиофизика и радиоастрономия, 2000)
Potentials of the backward-wave oscillator (BWO) with an inclined electron beam (the clinotron) as a source of electromagnetic radiation in THz regions are examined. A self-consistent collective electron-wave interaction theory is developed to study starting conditions and steady state oscillations of clinotron tubes. Optimization of the geometry of pulsed and continuous wave (CW) 1-THz clinotrons is carried out and a possibility of the development of promising tubes for this frequency region is found.